Pioneer performances staging the frontier - Rebhorn, Matthew (Oxford : Oxford University Press, 2012)
This volume offers a synoptic treatment of the history of American frontier performance ranging from Jacksonian America to Buffalo Bill's Wild West show at the Columbian Exposition of 1893. It reconceives how the frontier was, and still is, defined in performance, and what it means for that frontier to be called 'American'.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Theater -- United States -- History -- 19th century; American drama -- 19th century -- History and criticism; Frontier and pioneer life in literature; West (U.S.) -- In literature